Pendampingan Pada Nasabah di Unit Layanan Modal Mikro (ULAMM) PT PNM Persero Muara Bulian untuk Mengeliminasi Block Mental sebagai “Musuh” Utama Entrepreneur - Sumarni; Rohman William; Hendriyaldi; Nyimas Dian Maisyarah; Musyaiyadah (WIDA Publishing, 2022)
The number of business actors is an important indicator that will show whether a country is developed or not. The large number of entrepreneurs in a country will have an impact on the emergence of jobs which will automatically increase the country's economy. Indonesia experienced an increase of 3.1% of the total population. One of the Indonesian governments presenting PT PNM (Persero) is to contribute to the welfare of the community and advance Indonesian MSMEs, then the aim of PT PNM Persero ULaMM Muara Bulian is to form an entrepreneurial mentality, increase business and improve the economy, in line with the community service activities that will be carried out. The purpose of this service activity is to influence and change the mindset of customers who are